2001
DOI: 10.1111/j.1463-1318.2001.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of genito‐urinary dysfunction after surgery for colorectal cancer

Abstract: Objective To establish the incidence of impotence and urinary dysfunction after different forms of pelvic and colorectal surgery.Patients and methods Over a period of one year, 78 consecutive patients, mean age 66.8 years (range 43± 91 years), underwent surgery for colorectal cancer. Genito-urinary function was studied by clinical assessment and a postoperative questionnaire.Results Pre-operatively all males except one claimed to be potent. Of the 56 patients who had operations on the sigmoid colon and rectum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
2
Order By: Relevance
“…This suggested that low rectal cancer patients who underwent SLAR might complicate impotency and retrograde ejaculation in men and dyspareunia and decreased lubrication in women, but all were tolerable and did not markedly decrease the quality of life. Shah and Huddy [22] reported that of the 56 patients who had operations on the sigmoid colon and rectum, 12 (21.4%) developed urinary dysfunction, six (five males and one female) had increased frequency, while six (four females and two males) had stress incontinence. Borschitz et al [11] assessed the frequency of urinary bladder malfunctions by measuring residual urine volume using transcutaneous ultrasound before and after surgery, an increase in retained urine of more than 100 ml was found in 12 patients (15%), and neurogenic bladder was diagnosed in two (3%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This suggested that low rectal cancer patients who underwent SLAR might complicate impotency and retrograde ejaculation in men and dyspareunia and decreased lubrication in women, but all were tolerable and did not markedly decrease the quality of life. Shah and Huddy [22] reported that of the 56 patients who had operations on the sigmoid colon and rectum, 12 (21.4%) developed urinary dysfunction, six (five males and one female) had increased frequency, while six (four females and two males) had stress incontinence. Borschitz et al [11] assessed the frequency of urinary bladder malfunctions by measuring residual urine volume using transcutaneous ultrasound before and after surgery, an increase in retained urine of more than 100 ml was found in 12 patients (15%), and neurogenic bladder was diagnosed in two (3%).…”
Section: Discussionmentioning
confidence: 98%
“…This implied local recurrence rate increased against the distance between the lower margin of tumor and resection line, that is, a distal resection margin of 2 cm may be sufficient and that a margin of 1 cm is not adequate [17,18]. Fecal dysfunction included involuntary leakage of gas, liquid, and stool; and others were soiling, perianal rash, gas and feces discrimination, and capability to postpone evacuation [22][23][24][25]. Frequency of defecation is related to length of rectal stump; the intrinsic mechanism for the maintenance of continence following coloanal anastomosis is multifactorial and complex; manometric studies have shown that the capacity of the colon replacing the rectum is significantly reduced when compared with the normal rectum [2,18].…”
Section: Discussionmentioning
confidence: 99%
“…Originalien Funktionelle Harnblasenentleerungsstörungen nach Rektumoperationen werden häufig beobachtet und dennoch in der Fachliteratur kaum thematisiert [1][2][3][4][5][6][7][8][9]. Für die Miktionsstö-rungen werden unterschiedliche Faktoren verantwortlich gemacht.…”
Section: Harnblasenentleerungsstörungen Nach Rektumoperationenunclassified
“…Das Ausmaß einer Blasenfunktionsstörung nach Rektum operation hängt sowohl von der Ausprä gung und Lokalisation der Nervenschä digung als auch von einer Lageverände rung der Harnblase oder dem Auftreten einer perivesikalen Entzündung ab. Funk tionelle Harnblasenentleerungsstörungen nach Rektumoperation wurden in der Li teratur mit 0-41% beschrieben[1,[3][4][5][6][7][8].Mit unserer klinischen Studie an einem unizentrischen Patientenkollektiv wollen wir einen Beitrag zur Klärung von Inzi denz und Form von Blasenentleerungs störungen nach einer Rektumoperation leisten.V. Zugor · I. Miskovic · K. Matzel · W. Hohenberger · W. Neuhuber · A. Labanaris · G.E.…”
unclassified